Proceedings of the 6th International Conference on Multimodal Interfaces 2004
DOI: 10.1145/1027933.1027957
|View full text |Cite
|
Sign up to set email alerts
|

When do we interact multimodally?

Abstract: Mobile usage patterns often entail high and fluctuating levels of difficulty as well as dual tasking. One major theme explored in this research is whether a flexible multimodal interface supports users in managing cognitive load. Findings from this study reveal that multimodal interface users spontaneously respond to dynamic changes in their own cognitive load by shifting to multimodal communication as load increases with task difficulty and communicative complexity. Given a flexible multimodal interface, user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…The physical activity of manual or pen-based gesturing is believed 23 to play a particularly important role in organizing and facilitating people's spatial information processing, which has been shown to reduce cognitive load on tasks involving geometry, maps, and similar areas (Alibali et al, 2000;Oviatt, 1997) As task complexity increases, users self manage their working memory limits by distributing information across multiple modalities. As illustrated in Figure 3.3 (right), this represented an overall relative increase of +27% (Oviatt et al, 2004a). In one study, users' ratio of multimodal interaction increased as tasks became more difficult, from 59.2% during low-difficulty tasks, to 65.5% during moderate difficulty, 68.2% during high difficulty, and 75.0% on very high difficulty ones.…”
Section: Minimization Of Cognitive Loadmentioning
confidence: 88%
See 3 more Smart Citations
“…The physical activity of manual or pen-based gesturing is believed 23 to play a particularly important role in organizing and facilitating people's spatial information processing, which has been shown to reduce cognitive load on tasks involving geometry, maps, and similar areas (Alibali et al, 2000;Oviatt, 1997) As task complexity increases, users self manage their working memory limits by distributing information across multiple modalities. As illustrated in Figure 3.3 (right), this represented an overall relative increase of +27% (Oviatt et al, 2004a). In one study, users' ratio of multimodal interaction increased as tasks became more difficult, from 59.2% during low-difficulty tasks, to 65.5% during moderate difficulty, 68.2% during high difficulty, and 75.0% on very high difficulty ones.…”
Section: Minimization Of Cognitive Loadmentioning
confidence: 88%
“…During more difficult tasks, this impact of gesturing on reducing cognitive load increased (Goldin-Meadow et al, 2001). This effectively enhances their performance during both perception and production tasks (Calvert et al, 2004;Mousavi et al, 1995;Oviatt, 1997;Oviatt et al, 2004a;Tang et al, 2005). This effectively enhances their performance during both perception and production tasks (Calvert et al, 2004;Mousavi et al, 1995;Oviatt, 1997;Oviatt et al, 2004a;Tang et al, 2005).…”
Section: Minimization Of Cognitive Loadmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, previous research has shown that higher levels of cognitive load result in a significantly lower ROS (Oviatt, Coulston, & Lunsford, 2004;Jameson, Kiefer, Muller, Großmann-Hutter, Wittig, & Rummer, 2010).…”
Section: Speech Production and Rate Of Speechmentioning
confidence: 99%